-11w+w=-10

Simple and best practice solution for -11w+w=-10 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -11w+w=-10 equation:


Simplifying
-11w + w = -10

Combine like terms: -11w + w = -10w
-10w = -10

Solving
-10w = -10

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Divide each side by '-10'.
w = 1

Simplifying
w = 1

See similar equations:

| -2(p-10)+11=5 | | (x^2+8x)+16=25 | | 2(3x+4)=-16 | | -3d+-d=-20 | | 21k^3-18k^2+7k-6=0 | | 6x^3+15x^2-16x-40=0 | | -10+11u=2+8u | | 2y+-7=19 | | -(-5n+7)-1=2(n+5) | | -6m+18=-8m-20 | | -2=m-16/-1 | | (-0.2)(-0.58)= | | (x+5)(6x-7)=0 | | 7(7x+6)-x=8(4+6x) | | 3k=2k-16 | | f(x)=(2x-1)(x+2)(x+3) | | (7x-1)(x-7)=0 | | -4(w-7)=-7w+19 | | 18=3(j-13) | | 2(4+7x)=-3(1-4x)+5 | | 2u+38=7(u-1) | | r-10/3=3 | | .42/7.00=x/100 | | (2x-1)(2x+7)=0 | | 3(p-13)+4=13 | | x^5-ax^2-ax+1=0 | | -6(8v-4)=6(6v+4) | | n+9=4v-6 | | 8y=3x-12 | | 2(1+8x)=4(4x+8) | | ax+y=bx+K | | -6(4x-6)=-18-6x |

Equations solver categories